2017
DOI: 10.1186/s12906-017-1623-5
|View full text |Cite
|
Sign up to set email alerts
|

Anti-arthritic property of crude extracts of Piptadeniastrum africanum (Mimosaceae) in complete Freund’s adjuvant-induced arthritis in rats

Abstract: BackgroundRheumatoid arthritis, disease of unknown causes is a rheumatic and autoimmune pathology, recognised for its increasing frequency and its adverse consequences. It is a disease that occurs in most cases between 50 and 60 years and women are more affected than men. This study aimed at evaluating immunomodulatory and anti-arthritis capacity of aqueous and methanol extracts of stem bark of Piptadeniastrum africanum (Mimosaceae).MethodsROS production from phagocytes, proliferation of T-cells, TNF-α and IL-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(44 citation statements)
references
References 77 publications
5
39
0
Order By: Relevance
“…Results indicated that when taken the test extract daily can protect the body against inflammation and also used to treat an inflammatory condition. Results are in accordance with report by Mbiantcha et al [17].…”
Section: Resultssupporting
confidence: 93%
“…Results indicated that when taken the test extract daily can protect the body against inflammation and also used to treat an inflammatory condition. Results are in accordance with report by Mbiantcha et al [17].…”
Section: Resultssupporting
confidence: 93%
“…et al . (1982) 45,46 . In this experiment all the compounds were evaluated at 25 µg/mL, each in triplicate.…”
Section: Discussionmentioning
confidence: 99%
“…The CFA-induced arthritis model in experimental animals signify chronic inflammation involving several systemic changes along with synovial hyperplasia [154]. It results from massive leukocytes infiltration, increase in chemokine and cytokine levels including IL-1β and TNF-α, release of ROS, cartilage and bone destruction, along with swelling and deformation [154,155,156]. CFA injection into the footpad of rat causes swelling of periarticular tissues like ligaments and joint capsules.…”
Section: Anti-inflammatory Drug Development From Natural Products:mentioning
confidence: 99%